Health research knowledge translation into policy in Zambia: policy-maker and researcher perspectives - Annie Malama; Joseph Mumba Zulu; Selestine Nzala; Maureen Mupeta Kombe; Adam Silumbwe (BMC, 2021)
Abstract Background The translation of public health research evidence into policy is critical to strengthening the capacity of local health systems to respond to major health challenges. However, a limited amount of public health research evidence generated in developing countries is actually translated into policy because of various factors. This study sought to explore the process of health research knowledge translation into policy and to identify factors that facilitate or hinder the process in Zambia. Methods This work was an exploratory qualitative study comprising two phases. Firstly, a document review of health policies and strategic frameworks governing research was undertaken to understand the macro-environment for knowledge translation in Zambia. Secondly, key informant interviews were conducted with those responsible for health research and policy formulation. The study interviewed 15 key informants and a thematic analysis approach was used. Results The document review showed that there are policy efforts to promote knowledge translation through improvement of the research macro-environment. However, the interviews showed that coordination and linkage of the knowledge creation, translation and policy-making processes remains a challenge owing to lack of research knowledge translation capacity, limited resources and lack of knowledge hubs. Emerging local research leadership and the availability of existing stock of underutilized local health research data provide an opportunity to enhance knowledge translation to feed into policy processes in Zambia. Conclusions Public health research knowledge translation into policy remains a challenge in Zambia. To enhance the uptake of research evidence in policy-making, this study suggests the need for improved coordination, financing and capacity-building in knowledge translation processes for both health researchers and policy-makers.